2019
DOI: 10.3390/e21060608
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salient Crowd Motion Based on Repulsive Force Network and Direction Entropy

Abstract: This paper proposes a method for salient crowd motion detection based on direction entropy and a repulsive force network. This work focuses on how to effectively detect salient regions in crowd movement through calculating the crowd vector field and constructing the weighted network using the repulsive force. The interaction force between two particles calculated by the repulsive force formula is used to determine the relationship between these two particles. The network node strength is used as a feature para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Crowd movement has strong physical properties, so many works have applied physical models to analyze crowd videos [37]. Based on the physics properties, the methods of crowd behavior analysis can be expressed as fluid dynamics [38], energy, entropy models [39] and complex system science [40]. Among them, the fluid dynamics model has been widely used.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Crowd movement has strong physical properties, so many works have applied physical models to analyze crowd videos [37]. Based on the physics properties, the methods of crowd behavior analysis can be expressed as fluid dynamics [38], energy, entropy models [39] and complex system science [40]. Among them, the fluid dynamics model has been widely used.…”
Section: Related Workmentioning
confidence: 99%
“…Other methods are based on the fluid force model. Zhang et al [39] calculated the repulsive force based on the crowd vector field to construct a weighted network for salient crowd motion detection. Smoothed Particle Hydrodynamics (SPH), which was originally proposed by Gingold [31], is a meshless method for studying the motion characteristics of fluid particles.…”
Section: Related Workmentioning
confidence: 99%
“…They used CNN using self-attention mechanism so as to find the salient areas in human crowd images. Similarly, Zhang et al [ 106 ] were able to detect salient crowd motion using direction entropy and a repulsive force network. The frames of the crowd video sequence are evaluated by an optimal flow technique.…”
Section: Approachesmentioning
confidence: 99%
“…[ 24 ] used divergence measures, such as Kullback–Leibler (KL), between distributions of the data computed at different times in order to detect anomalies in big data streams. In [ 25 ], the authors suggested an entropy-based method to detect salient points in a crowd. This time, the entropy is used to measure the uncertainty of a particle motion direction, hence describing the chaotic degree of crowd motion.…”
Section: Introductionmentioning
confidence: 99%